Pengabdian Masyarakat dengan “Pendampingan Posyandu Remaja sebagai Upaya Preventif Kenakalan Remaja di Posyandu Remaja Kelurahan Banyurip Kota Pekalongan” - Ana Setyowati; Ida Baroroh; Swasti Artanti (LPPM Akbid Harapan Ibu Pekalongan, 2024)
Adolescence is a transition period which is a period of transition in a child's development between childhood and adulthood which generally begins at the age of 12 or 13 years and ends at the age of 21 years. Adolescence is a vulnerable period because of the inability of teenagers to solve their own problems. Many teenagers ultimately find that many of the solutions do not match their expectations. advances in science and technology always result in social change, with increasingly sophisticated communications technology, transportation and information systems, changes in society are accelerating more rapidly. In facing such situations, teenagers often have a more sensitive soul, which in the end, quite a few teenagers fall into things that are contrary to moral values, religious norms, social norms and norms of life in society. The aim of this service is to provide assistance to youth posyandu as an effort to prevent juvenile delinquency. The method used in this community service activity begins with an opening and introduction of the resource persons, then continues with the delivery of health education material, a question and answer session to the participants and finally closing. With this activity, the posyandu felt helped because it was provided with assistance and information in preventive efforts to prevent juvenile delinquency.